The Relationship between Procurement Officers, Project Management Success and Procurement Procedure in Ict Public Outsourcing: a Systematic Literature Review - Ahmad, Azran; Habibah Arshad, Noor; Ruzaini Syed Aris, Syaripah (International Journal of Engineering and Technology, 2018)
Obviously the use of Information Communication Technology (ICT) by organizations is increasing over the years, whether in government or the private sector. The use of ICT can be seen to increase efficiency and effectiveness of the services or products offered. To meet the demand of stakeholders today, ICT projects need to be developed through outsourcing. However the method of outsourcing has some issues that can affect the success of the development of ICT projects as has been much debated by previous studies. Yet, the discussion on project management success (PMS) factors that concentrate on the competency measurement for the department's officers who are managing the procurement process has not been sufficiently clarified. The aim of this Systematic Literature Review (SLR) is to identify the common attributes that influence project management success through the procurement procedure carried out by the procurement officer (PO). The outcome of the review explained the important relationship pattern between the identified attributes which will be applied in the future empirical and exploratory survey that will be carried out. Addition to this, the competency measurement model of ICT procurement officer to be developed.
Keywords: Project Management Success; Outsourcing; Procurement; Procurement Officer; Contract Management; ICT Project Management